2016
DOI: 10.3393/ac.2016.32.6.208
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Immunonutritional Status Changes During Preoperative Chemoradiation in Patients With Rectal Cancer

Abstract: PurposePrevious studies have demonstrated the prognostic impact of the prognostic nutritional index (PNI), a proposed indicator of immunonutritional statuses of surgical patients, on patients with various gastrointestinal cancers. Although the prognostic impact of the PNI on patients with colorectal cancer has been well established, its value has not been studied in patients treated with preoperative chemoradiation (pCRT). This study aimed to evaluate the prognostic impact of PNI on patients receiving pCRT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…However, this issue has been investigated in a group of 261 patients with locally advanced rectal cancer, where the patients were stratified arbitrarily into three groups according to the PNI difference (dPNI) between the neo-adjuvant CRT and pre-surgical measurements: dPNI < 5; dPNI of 5-10 and dPNI > 10; the dPNI was found to be firmly linked with survival outcomes. 47 Finally, our results ought not to be generalized to all stage IIIB NSCLC patients as they are restricted to a highly selected patients group with ECOG scores of 0-1, <80 years of age and BMI≥20 kg/m 2 .…”
Section: Discussionmentioning
confidence: 94%
“…However, this issue has been investigated in a group of 261 patients with locally advanced rectal cancer, where the patients were stratified arbitrarily into three groups according to the PNI difference (dPNI) between the neo-adjuvant CRT and pre-surgical measurements: dPNI < 5; dPNI of 5-10 and dPNI > 10; the dPNI was found to be firmly linked with survival outcomes. 47 Finally, our results ought not to be generalized to all stage IIIB NSCLC patients as they are restricted to a highly selected patients group with ECOG scores of 0-1, <80 years of age and BMI≥20 kg/m 2 .…”
Section: Discussionmentioning
confidence: 94%
“… 7 , 8 , 39 , 51 – 53 In addition, TRG was also correlated to the systemic inflammatory response and nutritional status. 54 , 55 Therefore, we further explored the relationship between FARI and response to NCRT. According to the survival analysis, TRG could not distinguish the patients with poor OS or DFS rates among all LARC patients ( Figure 6A and B , P=0.132 and P=0.499).…”
Section: Discussionmentioning
confidence: 99%
“…Onodera et al reported that a simplified PNI, which is based on only two laboratory parameters (albumin value and lymphocyte count), can be measured easily and used routinely in clinical practice (14). The serum albumin concentration reflects not only the patient's nutritional status but also chronic inflammation, and the serum lymphocyte count has been identified as an objective parameter of inflammation (20). Several reports have described low PNI at diagnosis as being an independent marker of poor outcomes for patients with various types of cancer (10,11,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The serum albumin concentration reflects not only the patient's nutritional status but also chronic inflammation, and the serum lymphocyte count has been identified as an objective parameter of inflammation (20). Several reports have described low PNI at diagnosis as being an independent marker of poor outcomes for patients with various types of cancer (10,11,20,21). PNI values greater than 50 were defined as normal, while those less than 50, 45, and 40 were regarded as mild, moderate-to-severe, and serious malnutrition, respectively (10).…”
Section: Discussionmentioning
confidence: 99%